2021
DOI: 10.1097/tp.0000000000003692
|View full text |Cite
|
Sign up to set email alerts
|

Frailty of the Heart Recipient

Abstract: Frailty has been defined as a state of increased vulnerability due to a decline in the reserve and function of multiple physiological systems. Initially conceived as a geriatric syndrome indicative of physiological aging, it is now apparent that frailty can also be observed as a manifestation of chronic disease states including heart failure. Estimates of the prevalence of frailty in heart failure vary according to the age of the study population and the frailty instrument used; however, multiple studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…Among the SOT recipients in this study, pre-frailty by the mFFI was present in 15 (44%) participants at 12 months post-transplant. This is similar in prevalence to the in-person assessment of physical frailty after lung, kidney, liver, or heart transplantation (Harhay et al, 2929; Jha et al, 2017 ; Lai et al, 2018 ; MacDonald, 2021 ; Varughese et al, 2020 ). The simple question about opening a jar may be an alternative to handgrip strength for evaluating muscle weakness remotely.…”
Section: Discussionsupporting
confidence: 66%
“…Among the SOT recipients in this study, pre-frailty by the mFFI was present in 15 (44%) participants at 12 months post-transplant. This is similar in prevalence to the in-person assessment of physical frailty after lung, kidney, liver, or heart transplantation (Harhay et al, 2929; Jha et al, 2017 ; Lai et al, 2018 ; MacDonald, 2021 ; Varughese et al, 2020 ). The simple question about opening a jar may be an alternative to handgrip strength for evaluating muscle weakness remotely.…”
Section: Discussionsupporting
confidence: 66%
“…However, Dent et al have identified 29 different frailty measures and comprehensively reviewed those in common use as well as individual factors such as gait speed ( 31 ). Macdonald et al have also summarised those tools relevant to heart transplantation and failure ( 33 ). A new clinical measure called the “Frail Trait Scale” (FTS) is currently being evaluated as part of the FRAILTOOLs project and has been shown to be one of the best tools for predicting a range of adverse outcomes in older people across clinical settings ( 34 ).…”
Section: Measurement Toolsmentioning
confidence: 99%
“…It is important to note that frailty is a dynamic process in these complex patients. For example, non-frail patients prior to transplant who have major complications requiring a long hospital admission post-transplant are likely to become frail post-operatively ( 33 ).…”
Section: Frailty In Mechanical Circulatory Support and Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators reported improvement of HGS after implantation of CF-LVAD [21,22]. Although it has been reported that frailty prior to BTT LVAD implantation is associated with an increased post-LVAD morbidity and mortality, it has also been reported that frailty is reversible in most patients who survive the perioperative period [45,46]. Maurer et al [47] assessed reversal of frailty in 29 elderly frail LVAD recipients with a mean age of 71 years.…”
Section: Impact Of Lvad Implantation On Sarcopeniamentioning
confidence: 99%